An Optical Sensor Array Discriminates Syrups and Honeys. Issue 17 (28th February 2018) - Bojanowski, N. Maximilian; Hainer, Felix; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F.
Abstract: We report a cross‐reactive sensor array, combining a two‐component probe system based upon three viologen substituted boronic acids and a poly(aryleneethynylene) (PAE) and an additional number of simple PAEs alone. This combined system discriminates 27 different honeys in aqueous solution, according to patterns in fluorescence intensity modulation, using linear discriminant analysis for data processing. The fluorescence turn‐on array detects saccharide composition, while the PAEs discriminate trace colored components in the honeys. Abstract : Sweet on the tongue : A poly(aryleneethynylene) tongue that discriminates different honeys works through complex formation with different boronic‐acid‐substituted viologens.